The problem of suicide - Rodante, Demián E. (Revista del Hospital Italiano de Buenos Aires, 2024)
Letter to the editor about the work of Mlleza et al. "Multidimensional Analysis of Clinical, Demographic, and Cultural Factors in Suicidal Ideation and Behavior in a Psychiatric Inpatient Ward".
Keywords: editorial; suicide